Contribution of Somatic and Dendritic SK Channels in the Firing Rate of Deep Cerebellar Nuclei: Implication in Cerebellar Ataxia - Samira Abbasi; Ataollah Abbasi; Yashar Sarbaz; Parviz Shahabi (Basic and Clinical Neuroscience, 2016)
Introduction: Loss of inhibitory output from Purkinje cells leads to hyperexcitability of the Deep Cerebellar Nuclei (DCN), which results in cerebellar ataxia. Also, inhibition of small-conductancecalcium-activated potassium (SK) channel increases firing rate  f DCN, which could cause cerebellar ataxia. Therefore, SK channel activators can be effective in reducing the symptoms of this disease, and used for the treatment of cerebellar ataxia. In this regard, we hypothesized that blockade of SK channels in different compartments of DCN would increase firing rate with different value. The location of these channels has different effects on increasing firing rate.